The Influence of Employee Hospitality and Price Perception on Revisit Intention in Tanjung Duriat Sumedang - Ahmad Muzadi; Supriyadi, Tedi; Sukirman, Oman (Universitas Muhammadiyah Pontianak, 2026)
This study examines the influence of employee hospitality and price perception on revisit intention at Tanjung Duriat, Sumedang. A quantitative survey was conducted with 399 respondents, analyzed using multiple linear regression in SPSS. The results show that employee hospitality and price perception significantly affect revisit intention, both partially and simultaneously, with a contribution of 48.9%. Price perception has a stronger influence than hospitality. These findings imply that improving service quality and implementing fair, value-based pricing are essential strategies to enhance tourist loyalty and ensure sustainable destination competitiveness. Keywords: Employee Hospitality; Price Perception; Revisit Intention; Tourist Loyalty; Service Quality; Value-Based Pricing; Tourism Destination; Sustainable Tourism